2023
DOI: 10.1161/circulationaha.122.063372
|View full text |Cite
|
Sign up to set email alerts
|

Orally Bioavailable Macrocyclic Peptide That Inhibits Binding of PCSK9 to the Low Density Lipoprotein Receptor

Abstract: Background: Inhibition of PCSK9 (proprotein convertase subtilisin/kexin type 9)-low density lipoprotein receptor interaction with injectable monoclonal antibodies or small interfering RNA lowers plasma low density lipoprotein-cholesterol, but despite nearly 2 decades of effort, an oral inhibitor of PCSK9 is not available. Macrocyclic peptides represent a novel approach to target proteins traditionally considered intractable to small-molecule drug design. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…15 The cyclic peptide MK-0616 may present an alternative to currently available PCSK9 inhibitors, especially for patients who prefer oral medications or who cannot access the subcutaneous formulations. In the study by Johns et al, 11 MK-0616 demonstrated the ability to effectively decrease LDL-C levels, both as monotherapy and in combination with statin treatment. According to the data on other PCSK9 inhibitors, it is likely that MK-0616 will also prove to be effective in preventing cardiovascular disease and reducing the incidence of adverse cardiovascular events.…”
Section: Article See P 144mentioning
confidence: 99%
See 1 more Smart Citation
“…15 The cyclic peptide MK-0616 may present an alternative to currently available PCSK9 inhibitors, especially for patients who prefer oral medications or who cannot access the subcutaneous formulations. In the study by Johns et al, 11 MK-0616 demonstrated the ability to effectively decrease LDL-C levels, both as monotherapy and in combination with statin treatment. According to the data on other PCSK9 inhibitors, it is likely that MK-0616 will also prove to be effective in preventing cardiovascular disease and reducing the incidence of adverse cardiovascular events.…”
Section: Article See P 144mentioning
confidence: 99%
“…Furthermore, 2 phase 1 studies were performed to evaluate the pharmacodynamics and safety profile of MK-0616 in humans. 11 In the first study, 60 healthy male volunteers received a single-ascending dose of the drug, whereas the second study tested a multiple-risingdose regimen in statin-treated patients. In the first study, participants were given a single dose during a specific period.…”
Section: Article See P 144mentioning
confidence: 99%
“…17 In turn, Merck recently disclosed the structure of MK-0616, an oral proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitor, which in a recent Phase 2b study, significantly reduced LDL-C in patients with hypercholesterolemia. 18 Potency and protease stability were obtained through introduction of a fluorinated tryptophan, D-Ala (AA2), α-Me-Pro (AA8), and cross-linking, ultimately yielding an oral MP inhibitor at a fraction of the size of current monoclonal antibody injectables.…”
mentioning
confidence: 99%
“…For Chugai, their first clinical macrocyclic peptide for intracellular rat sarcoma virus (RAS) inhibition was identified through incorporation of multiple N -substituted ncAAs, reducing the polar surface area and improving membrane permeability . In turn, Merck recently disclosed the structure of MK-0616, an oral proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitor, which in a recent Phase 2b study, significantly reduced LDL-C in patients with hypercholesterolemia . Potency and protease stability were obtained through introduction of a fluorinated tryptophan, d -Ala (AA2), α-Me-Pro (AA8), and cross-linking, ultimately yielding an oral MP inhibitor at a fraction of the size of current monoclonal antibody injectables.…”
mentioning
confidence: 99%
“…An error has been identified in Figure regarding the structure and caption of MK-0616 ( 5 ). The functional group on the terminal aryl is incorrectly depicted as −OH; the correct functional group is −OCH 3 on the terminal aryl ring. , The corrected Figure is shown below:…”
mentioning
confidence: 99%